Model Analisis Prediksi Kebangkrutan Bank Swasta Nasional Periode 2002-2006 - Agha Swara Ganesha; Tomy G. Soemapradja; Darman Darman; Desmizar Desmizar (Bina Nusantara University, 2012)
There are two main objectives to be achieved by this study:to determine the accuracy level of prediction models of health national private banks using CAMEL ratios, and model the value of Z for the national private commercial banks by using multiple discriminant analysis (MDA) as well as Altman Z values on the model. Determination of the model using the Z value ratios banking health of Capital, Assets, Earnings and Liability (CAEL), then create a new Z value model specifically for national private commercial bank in Indonesia by using statistical analysis of MDA, with SPSS. The samples used were 30 banks, consisting of 19 survived banks in 2002 and 11 bankrupt banks in the same year. The results showed that the model value of Z in the year 2003-2006 cannot reach good accuracy when measured on a per year. Instead, the new Z value model generated by this study has better accuracy in predicting the rate of bankruptcy cases nationwide private commercial bank in Indonesia (86.7%) in 2002 and an average accuracy of 71.67% for the 4-year period of the review.